2021
DOI: 10.1017/inp.2021.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carrier volume and application method on waterhyacinth (Eichhornia crassipes) response to 2,4-D, glyphosate, and diquat

Abstract: Mesocosm studies were conducted in 2020 to evaluate the effects of carrier volume and application method on waterhyacinth response to 2,4-D, glyphosate, and diquat. Carrier volumes of 935, 467, and 187 L ha-1 were applied using either a conventional stream, conventional cone, adjustable cone, or a drizzle stream spray pattern. Reducing carrier volume from 935 L ha-1 reduced spray coverage up to 60% depending on application method. However, reducing carrier volume did not diminish efficacy of any herbicide or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The data in this study suggest that aerial applications would promote greater spray retention and reduced spray loss relative to a standard highvolume hand-gun application. Furthermore, there is evidence of decreased carrier volumes resulting in increased efficacy of systemic herbicides in some aquatic species (Sperry and Ferrell 2021; Van et al 1986). It has been speculated that those herbicides in aquatics that possess in-water activity require a fraction of the intended herbicide rate to be absorbed by below-water structures; however, this theory has not been directly tested (Sperry and Ferrell 2021).…”
Section: Carrier Volumementioning
confidence: 99%
See 3 more Smart Citations
“…The data in this study suggest that aerial applications would promote greater spray retention and reduced spray loss relative to a standard highvolume hand-gun application. Furthermore, there is evidence of decreased carrier volumes resulting in increased efficacy of systemic herbicides in some aquatic species (Sperry and Ferrell 2021; Van et al 1986). It has been speculated that those herbicides in aquatics that possess in-water activity require a fraction of the intended herbicide rate to be absorbed by below-water structures; however, this theory has not been directly tested (Sperry and Ferrell 2021).…”
Section: Carrier Volumementioning
confidence: 99%
“…Furthermore, there is evidence of decreased carrier volumes resulting in increased efficacy of systemic herbicides in some aquatic species (Sperry and Ferrell 2021; Van et al 1986). It has been speculated that those herbicides in aquatics that possess in-water activity require a fraction of the intended herbicide rate to be absorbed by below-water structures; however, this theory has not been directly tested (Sperry and Ferrell 2021). For other herbicides that do not exhibit in-water activity, such as glyphosate or imazapyr (UF 2018), it is assumed that any spray solution that is not retained on above-water plant material does not contribute to plant uptake through the water column and, ultimately, to death.…”
Section: Carrier Volumementioning
confidence: 99%
See 2 more Smart Citations
“…This is likely due to concentrated herbicide spray solutions at lower carrier volumes, whereas more carrier (i.e., water) dilutes the herbicide and potentially increases runoff of spray solution. Previous research on carrier volume effects on herbicide efficacy for aquatic plant species has shown that decreased carrier volumes can increase efficacy, depending on the target species and herbicide being used (Van et al 1986;Willard et al 1998;Nelsonetal.2007;Sperry and Ferrell 2021). Additionally, Van et al (1986) reported that glyphosate applications to waterhyacinth exhibited 33% greater spray retention at a carrier volume of 467 L ha −1 compared to 935 L ha −1 .…”
Section: Adjuvant Typementioning
confidence: 99%